Familial prostate cancer - Giri, Veda N. (Semin Oncol, 2016)
Prostate cancer is the most commonly diagnosed cancer among men in the United States as well as most Western countries. A significant proportion of men report having a positive family history of prostate cancer in a first-degree relative (father, brother, son), which is important in that family history is one of the only established risk factors for the disease and plays a role in decision-making for prostate cancer screening. Familial aggregation of prostate cancer is considered a surrogate marker of genetic susceptibility to developing the disease, but shared environment cannot be excluded as an explanation for clustering of cases among family members. Prostate cancer is both a clinically and genetically heterogeneous disease with inherited factors predicted to account for 40%–50% of cases, comprised of both rare highly to moderately penetrant gene variants, as well as common genetic variants of low penetrance. Most notably, HOXB13 and BRCA2 mutations have been consistently shown to increase prostate cancer risk, and are more commonly observed among patients diagnosed with early-onset disease. A recurrent mutation in HOXB13 has been shown to predispose to hereditary prostate cancer (HPC), and BRCA2 mutations to hereditary breast and ovarian cancer (HBOC). Genome-wide association studies (GWAS) have also identified approximately 100 loci that associate with modest (odds ratios < 2.0) increases in prostate cancer risk, only some of which have been replicated in subsequent studies. Despite these efforts, genetic testing in prostate cancer lags behind other common tumors like breast and colorectal cancer. To date, National Comprehensive Cancer Network (NCCN) guidelines have highly selective criteria for BRCA1/2 testing for men with prostate cancer based on personal history and/or specific family cancer history. Tumor sequencing is also leading to the identification of germline mutations in prostate cancer patients, informing the scope of inheritance. Advances in genetic testing for inherited and familial prostate cancer (FPC) are needed to inform personalized cancer risk screening and treatment approaches.